PENGEMBANGAN BOARDGAME UTASI TERINTEGRASI APLIKASI GOOGLE SLIDES DALAM PEMBELAJARAN IPS PADA SISWA KELAS V DI MI HUSNUL KHATIMAH KOTA SEMARANG - Sari, Deni Modeana; Rasimin, Rasimin (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
This study aims to develop a board game integrated with google slides application in social studies learning. The type of research used is Research and Development (RD) with the research subjects being teachers and students of MI Husnul Khatimah Semarang City. The data collection instruments used questionnaires, interviews, tests, and documentation.  The boardgame development process in this study used the Borg and Gall model (Potential and problems, Data collection, Product design, Product validation, Product improvement, Product trial, Product revision, Product revision, Product revision). The product is developed according to the initial conditions and then tested for feasibility and revised until it is suitable for implementation in learning. The results of the feasibility test / validation of media experts get an average percentage of 93%, social studies material experts as much as 85%. Based on the results of each validator shows that the boardgame integrated google slides application in social studies learning is feasible to use. The effectiveness of the boardgame integrated google slides application in social studies learning is shown from the results of the calculation of the t test on the pretest and posttest scores of students. Paired Samples Statistics results show the t value of 0.000 0.05, then Ha is accepted and Ho is rejected. There is a significant difference between pretest and posttest data, so it can be concluded that the development of board games integrated with google slides application in social studies learning is effective for improving the learning outcomes of fifth grade students of MI Husnul Khatimah Semarang City.